2006
DOI: 10.1080/0300443042000302618
|View full text |Cite
|
Sign up to set email alerts
|

Training community‐based professionals to implement an empirically supported parenting program

Abstract: Professionals representing 14 community-based organizations were trained at three different sites serving urban and rural families to implement an empirically supported parenting program for families of young children with challenging behaviors. Of the 44 practitioners trained, 23 successfully completed the program, which involved passing a knowledge test and facilitating the entire 10session program with a family. A total of 28, primarily NOT THE PUBLISHED VERSION; this is the author's final, peer-reviewed ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…On the other hand, it was concluded that there was no significant effect on messages, nonverbal communication, or the care and health sub-dimensions of mothers. This result obtained from the studies reflects the findings of other studies conducted in Turkey and abroad (Bağatarhan, 2012;Çağdaş et al, 2010;Elibol, 2007;Evirgen, 2002;Fox et al, 2006;Landy & Menna, 2006;MacPhee & Miller-Heyl, 2003;Naik-Polan, 2004;Öğretir & Demiriz, 2009;Özel & Zelyurt, 2016;Reid et al, 2004;Sala Razı, 2004;Simpkins et al, 2006;Yalçın, 2013;Temiz, 2014;Uçar Çabuk, 2017).…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, it was concluded that there was no significant effect on messages, nonverbal communication, or the care and health sub-dimensions of mothers. This result obtained from the studies reflects the findings of other studies conducted in Turkey and abroad (Bağatarhan, 2012;Çağdaş et al, 2010;Elibol, 2007;Evirgen, 2002;Fox et al, 2006;Landy & Menna, 2006;MacPhee & Miller-Heyl, 2003;Naik-Polan, 2004;Öğretir & Demiriz, 2009;Özel & Zelyurt, 2016;Reid et al, 2004;Sala Razı, 2004;Simpkins et al, 2006;Yalçın, 2013;Temiz, 2014;Uçar Çabuk, 2017).…”
Section: Discussionsupporting
confidence: 87%
“…At the end of the program, the findings of the research; found that the informative counseling program applied to young people had a significant effect on the levels of conflict between adolescents and fathers, and this finding supports the findings of our study. Fox, Duffy and Keller (2006), who prepared a training program for mothers and fathers in order for parents to cope with the problematic behaviors of their children, gave information to parents about communication skills, especially for their children to cope easily with behavioral problems. Research findings show that parents' parenting skills have developed after the training program and they can cope more easily with the problematic behaviors of their children.…”
Section: Discussionmentioning
confidence: 99%
“…The YJB sample excludes those who dropped out, never attended or never requested the intervention (Ghate and Ramella, 2002). In fact, dropping out and poor uptake are generic difficulties for PPs (Fox et al , 2006; Scott et al , 2006). Finally, while both Department for Children, Schools and Families and YJB provide guidelines that highlight the importance of the EB, neither goes as far as recommending that service commissioners should select EB programmes (Relate, 2005; YJB, 2008).…”
Section: Introductionmentioning
confidence: 99%